Development of a Plastic Waste Management Guideline Book at the Baitul Hikmah Islamic Boarding School, Tempurejo, Jember - Warohmah, Eka Widianti; Nurjanah, Umi; Afandi, Beny (Universitas Islam Jember, 2025)
This research is motivated by the lack of media in managing plastic waste at the Baitul Hikmah Islamic Boarding School. So far, in handling plastic waste, only folding the waste has been implemented and is only valid for a few months. This research was conducted to overcome plastic waste in the Islamic Boarding School’s Surrounding. The subject of assessment in this guideline book media is for validators of material experts and media experts as well as student responses questionnaires. The type of research used is research and development which refers to the 4-D model which consists of 4 stages, namely: Define, Design, Develop and Disseminate. The results of the consultation are used to improve before being validated by expert’s media and material. Based on the test results from the expert validator’s material, it can be concluded that this media obtained a value of 91.66% with a feasible category, and the test results from the expert validator’s media obtained a value of 87.5% with a feasible category. Then continued to the last stage, namely the distribution of the guidebook, by conducting a response test to students and administrators of the cleaning section with an overall value of 100% with a category of strongly agree. As well as the socialization of the guidebook and duplicated as many as 10 books to members of Bersih Lingkungan (BERLIN) and administrators of Ikatan Santti Baitul Hikmah (ISBAH) for the cleaning section. Based on this description, it can be concluded that this guidebook media is very feasible to be used as a learning medium in handling waste at the Baitul Hikmah Islamic Boarding School, especially plastic waste.